Diversity and population sizes of wintering waterbirds in the wetlands of the Saïss-Middle Atlas Region (North-Central Morocco): main survival factors and evaluation of habitat loss - Squalli, Wafae; Mansouri, Ismail; Douini, Ikram; Achiban, Hamid; Saghrouchni, Hamza; El Agy, Abdelbari; Fadil, Fatima; Wink, Michael; Dākkī, Muḥammad (Animals, 2024)
Moroccan wetlands host up to half a million wintering birds and provide a stopover for tens of thousands of migrants, while they are inhabited by few nesting species. Most of this avifauna prefers to use the large coastal wetlands or reservoirs, while many species are dispersed across hundreds of small inland wetlands of various types. In this study, we monitored the wintering avifauna of 11 wetlands of the Saïss plain and its adjacent Atlas Mountains (north-center of Morocco), during six wintering seasons (2017-2018 to 2022-2023), with the objective of assessing the importance of this region as a waterbird wintering area. Using the richness of the species, we determine the bird population changes during this pentad and between the different types of wetlands (natural, human-made, and natural wetlands). During this study, we recorded 51 species, belonging to 17 families, among which exist four remarkable birds: the endangered Oxyura leucocephala, the vulnerable Aythya ferina and the near-threatened Aythya nyroca and Limosa limosa. Bird diversity is higher in human-made ecosystems than in peri-urban and natural ecosystems, while the populations’ size is similar in urban and non-urban wetlands. With regard to bird conservation, these inland wetlands, mainly the small ones, are threatened by recurrent droughts and various anthropic stressors, which we describe using our observations of the two last decades (2003-2023). The loss of habitat is significant, reaching 348.5 hectares, while the impacts of reduced precipitation and temperature increase are particularly evident in the mountainous natural lakes.
Gesehen am 14.11.2024